Inhibition of BRD4 activates the AKT-SIRT3 signaling pathway to suppress apoptosis and attenuate hyperoxia-induced lung injury - Qin, Kangjie; Zheng, Jie; Zhang, Yuting; Wang, Yiyu; Qin, Han; Dai, Qiuyu; Liu, Xinxin; Cheng, Liting; Yu, Kun; Chen, Miao; Qin, Song (Frontiers in Bioengineering and Biotechnology, 2025)
As a critical pulmonary complication in oxygen therapy, hyperoxia-induced lung injury (HILI) is featured with edema, alveolar wall thickening, and inflammatory cell infiltration. Bromodomain containing 4 (BRD4) has been documented as a vital regulator of apoptosis, inflammation, and oxidative stress under various pathological conditions. However, whether BRD4 plays a part in HILI has not yet been well investigated. The current investigation revealed a significant elevation of BRD4 expression in both in vitro and in vivo models of HILI. Notably, BRD4 knockdown effectively attenuated apoptosis, oxidative stress, and inflammatory response in H2O2-challenged AEC-II cells. Further investigation elucidated that BRD4 knockdown activated the AKT signaling pathway and upregulated SIRT3 expression in vitro and in vivo. AKT inhibition markedly abrogated BRD4 silencing-mediated AKT activation and SIRT3 upregulation in AEC-II cells exposed to H2O2, while SIRT3 inhibition failed to alter AKT activation. In addition, AKT inactivation also reversed BRD4 inhibition-mediated increased in the transcriptional activity of SIRT3. Furthermore, AKT inactivation or SIRT3 inhibition significantly diminished the protective effects of BRD4 knockdown on H2O2-treated AEC-II cells. In summary, this work elucidated that BRD4 inhibition ameliorates HILI through AKT-mediated SIRT3 upregulation. Our study highlights the vital role of the BRD4/AKT/SIRT3 axis in mediating HILI and suggests BRD4 as an attractive target for HILI management.